A Survey about the Pronunciation of [v] on Japanese University Student - แย้มสุขเสรี, ปฐมพร (FOYER: The Journal of Humanities, Social Sciences, and Education, 2018)
For a long time, the [v] sound in English was represented by [b] sound in Japanese Katakana notation, both in written form and pronunciation. However, recently there is a new Katakana notation dedicated to transcribing foreign [v] sounds, which is gradually being used more in writing, as can be seen on the Internet, in magazines etc. For pronunciation, since there is no [v] sound in Japanese language, even if the new Katakana notation for English [v] sound is being used in writing, native Japanese Speakers still tend to pronounce [b] for [v]. A survey was conducted to investigate whether Japanese speakers pronounced [b] and [v] differently. The results showed that a number of loan words are still pronounced with [b] sound as established wordforms. Nevertheless, interchange of [b] and [v] was observed. One of the factors considered influencing pronunciation is Katakana notation of that words. Native Japanese Speakers tend to unify their pronunciation with Katakana notation. Also, native Japanese Speakers can create their image by choosing to pronounce [b] or [v] which can lead to an explanation about Japanese sociolinguistics.